Trichodysplasia spinulosa: Case reports and review of literature. Issue 5 (16th June 2020) - Jose, Aju; Dad, Taimur; Strand, Andrew; Tse, Julie Y.; Plotnikova, Natalia; Boucher, Helen W.; Sarnak, Mark J.; Gilbert, Scott J.; Goyal, Nitender
Abstract: Trichodysplasia spinulosa (TS) is a rare skin condition caused by trichodysplasia spinulosa‐associated polyomavirus (TSPyV). It affects immunosuppressed patients, and <50 cases have been reported. The majority of these cases are seen in solid organ transplant recipients. TS often poses a diagnostic and therapeutic challenge because of its rarity and resemblance with other skin conditions. Several forms of treatment are usually tried prior to establishing a definitive diagnosis. Oral valganciclovir and topical cidofovir have been found to give the best results and hence are the most commonly used agents once the diagnosis is established. Here, we present two cases with a review of literature of TS in solid organ transplant recipients, focusing on time to develop the condition post‐transplant, immunosuppression regimen used, and treatment initiated both before and after a definitive diagnosis.